Selectivity and Sociality: Aggression and Affiliation Shape Vole Social Relationships - Lee, Nicole S.; Beery, Annaliese K. (Frontiers in Behavioral Neuroscience, 2022)
The formation of selective social relationships is not a requirement of group living; sociality can be supported by motivation for social interaction in the absence of preferences for specific individuals, and by tolerance in place of social motivation. For species that form selective social relationships, these can be maintained by preference for familiar partners, as well as by avoidance of or aggression toward individuals outside of the social bond. In this review, we explore the roles that aggression, motivation, and tolerance play in the maintenance of selective affiliation. We focus on prairie voles (Microtus ochrogaster) and meadow voles (Microtus pennsylvanicus) as rodent species that both exhibit the unusual tendency to form selective social relationships, but differ with regard to mating system. These species provide an opportunity to investigate the mechanisms that underlie social relationships, and to compare mechanisms supporting pair bonds with mates and same-sex peer relationships. We then relate this to the role of aggression in group composition in a comparative context.